La angustia de vivir en Comala. Entre la añoranza y el desamparo - Enciso, Julia; Pérez, Miguel José (Didáctica. Lengua y Literatura, 2003)
Here do we expose the helplessness situation in which Comala’s inhabitants are: on the one hand, because of Pedro Páramo’s economic and psichological tyranny and the sexual violence that both Pedro and his son Miguel practise on them; and, on the other, because of Priest/Father Rentería’s oppression, whose religion is imposed on them based upon superstition and fear.